The Correlation between Lipase Activity and the Production of Fatty Acids of PBC Cocoa Clone - Abd Samah, Othman; Karrupan, Jeevan; Syed, Mohd Arif (Universiti Putra Malaysia Press, 1998)
A study was carried out to determine the correlation between lipase activity in cocoa beans and the presence of free fatty acids which could affect the aroma and flavour of cocoa. Lipase activity fell from 0.46 to 0.15 ~mol/min/mg protein during six days of fermentation. Changes in the pH from 6.6 to 5.1 in the cotyledon and the increase in temperature seems to have contributed to the decrease in lipase activity, although no consistent correlation was observed. Maximum acetic acid production was observed on the third day of fermentation, when the maximum temperature was attained by the cocoa beans. However, other fatty acids increased continuously until the fifth day of fermentation and declined thereafter.